Quantitative magnetic resonance imaging as marker of synovial membrane regeneration and recurrence of synovitis after arthroscopic knee joint synovectomy: a one year follow up study. Issue 3 (1st March 2001) - Østergaard, M; Ejbjerg, B; Stoltenberg, M; Gideon, P; Volck, B; Skov, K; Jensen, C Hjorth; Lorenzen, I
Abstract : OBJECTIVES: By repeated magnetic resonance imaging (MRI) to study synovial membrane regeneration and recurrence of synovitis after arthroscopic knee joint synovectomy in patients with rheumatoid arthritis (RA) and other (non-RA) causes of persistent knee joint synovitis. METHODS: Contrast enhanced MRI was performed in 15 knees (nine RA, six non-RA) before and one day, seven days, two months, and 12 months after arthroscopic synovectomy. Synovial membrane volumes, joint effusion volumes, and cartilage and bone destruction were assessed on each MRI set. Baseline microscopic and macroscopic assessments of synovitis and baseline and follow up standard clinical and biochemical examinations were available. RESULTS: Synovial membrane and joint fluid volumes were significantly reduced two and 12 months after synovectomy. However, MRI signs of recurrent synovitis were already present in most knees at two months. No significant differences between volumes in RA and non-RA knees were seen. Synovial membrane volumes at two months were significantly inversely correlated with the duration of clinical remission, for all knees considered together (Spearman's correlation r s =−0.67; p<0.05), for RA knees ( r s =−0.76; p<0.05), and for non-RA knees ( r s =−0.83; p<0.05). Baseline volumes were not significantly correlated with clinical outcome. Only three knees (all RA) showed erosive progression. The rate of erosive progression was not correlated with MRI volumes or with clinical or biochemical parameters. CONCLUSION: The synovial membrane had regenerated two months after arthroscopic knee joint synovectomy and despite significant volume reductions compared with baseline it often showed signs of recurrent synovitis. MRI seems to be valuable as a marker of inflammation, destruction and, perhaps, as a predictor of therapeutic outcome in arthritis.